AYURVEDIC MANAGEMENT OF CERVICAL EROSION THROUGH YONI PRAKSHALAN AND JATYAADI TAIL PICHU: A PILOT STUDY - Pravesh, Tomar; Saloni, *Garg (International Journal of Ayurveda and Pharma Research, 2017)
Introduction: Ectropion is defined as erosion, eversion of cervical mucosa and is usually associated with leucorrhea due to chronic endocervicitis. It is seen as red circular, granular surface surrounding the cervical Os bathed in discharges. Separate description of cervical erosion is not available in Ayurveda classics. On study of etiological factors and sign and symptoms of the disease it is found to be caused by Kapha Pitta Dosha Prakopa affecting Yoni and Garbahshayamukha leading to Samprapti which further manifests as cervical erosion. Based on the effecting Doshas and etiological factors the therepy is selected i.e., Yoniprakshalan with Panchvalkalkwath and Jatyaaditail Pichu. Both are Kapha Pittashamak and have curative effects on sign and symptoms of cervical erosion. Material and Methods: A total 10 patients were selected from department of Prasuti Tantra and Stree Roga based on diagnostic, exclusion and inclusion criteria. Yoniprakshalan with 250 ml Panchvalkal Kwatha and Pichu with Jatyaadi Tail done for 7 days in three consecutive cycles. Results: Highly significant results (p<0.0001) were obtained on amount of discharges, color of erosion and cervical tenderness. Area covered by erosion decreased significantly after treatment. Overall effect of the therapy includes marked improved in 50 % of the patients. Conclusion: The therapy proved to be an effective measure in the management of cervical erosion. Clinical trial with large no of population should be done in future to see further effects of the therapy and to establish successful Ayurvedic management of this highly prevalent disease of the women in present world.